Improvement of cost performance accompanied by quality control using value engineering and six sigma methods in high-rise building project - Rochman, Khairul; Susetyo, Budi (International Journal of Engineering and Technology, 2020)
Construction projects are unique, complex, and have high risks, thereby increasing priorities. The application of the concept of mega con-struction with the risk of increasing costs needs to be eliminated by the value engineering and quality control methods. Re-analyzing a de-velopment plan is an option to save costs, but still in accordance with applicable specifications and conditions. Quality control with the six sigma method can be defined as relating to systemic and systematic to identify and eliminate waste or activities that are not added activities that do not add value, radical continuous improvement to achieve six sigma performance levels, by flowing products (material, work-in-process, output) and information using a Pull system from internal and external users to achieve goals and perfection with only produce a small amount for every one million opportunity or operation. The results of the case study conducted on the upper structure work (column and beam) based on the design value of the multi-storey building obtained a cost efficiency of 9.27% and 3.19% of the initial cost design. Whereas the implementation of six sigma is used to reduce work defects from excessive targets and low worker skills. NCR from this high-rise building project, obtained a value of 39 defects, with a Disability Per Million Opportunity value of 3.125 DPMO, which after being converted to a sigma table, is included in the 4.23 sigma category and a DMAIC (Define-Measure-Analyze-Improve-Control) in order to maintain quality and reduce defects resulting from upper structure work.Â Â